2019
DOI: 10.1080/03601234.2018.1550299
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal activity of P3HB microparticles containing tebuconazole

Abstract: In this study, tebuconazole (TEB)-loaded poly-3-hydroxybutyrate (P3HB)-based microparticles were developed and comprehensively characterized. TEB-loaded microparticles (10, 25, and 50%) were prepared using double emulsification technique. Encapsulation efficiency of TEB varied from 59 to 86%. As the loading amount was increased, the average diameter of microparticles increased too, from 41.3 to 71.7 µm, while zeta potential was not influenced by TEB loading, varying between -32.6 and -35.7 mV. TEB was released… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…50,51 The effect of the concentration of the active ingredient was demonstrated in a study by Shershneva et al: the average diameter of P(3HB)/tebuconazole microparticles increased from 41.3 to 71.7 μm as tebuconazole concentration was increased from 10% to 50%. 43 Other authors also reported size heterogeneity of nanoparticles (261.9 ± 35.1 nm) prepared from the P (3HB/3HV) copolymer and loaded with paclitaxel 50 and PLGA composite particles, whose size varied from 220 to 500 nm. 51 The microparticles based on the lowcrystallinity P(3HB/4HB) copolymers and loaded with the trifluralin herbicide were smaller, and their size was less variable (2.5 to 4.0 μm).…”
Section: Characterization Of the Microparticlesmentioning
confidence: 92%
See 4 more Smart Citations
“…50,51 The effect of the concentration of the active ingredient was demonstrated in a study by Shershneva et al: the average diameter of P(3HB)/tebuconazole microparticles increased from 41.3 to 71.7 μm as tebuconazole concentration was increased from 10% to 50%. 43 Other authors also reported size heterogeneity of nanoparticles (261.9 ± 35.1 nm) prepared from the P (3HB/3HV) copolymer and loaded with paclitaxel 50 and PLGA composite particles, whose size varied from 220 to 500 nm. 51 The microparticles based on the lowcrystallinity P(3HB/4HB) copolymers and loaded with the trifluralin herbicide were smaller, and their size was less variable (2.5 to 4.0 μm).…”
Section: Characterization Of the Microparticlesmentioning
confidence: 92%
“…The average diameter of P(3HB) particles loaded with the tebuconazole fungicide ranged between 41 ± 11.2 and 71.0 ± 10.9 μm. 43 The sizes of the P(3HB) and P(3HB/3HV) microparticles loaded with ametryn were 10.6 ± 0.43 and 20.5 ± 0.93 μm, respectively. 39 Another study showed the effect of the 3HB to 3HV ratio in the copolymer, which varied between 24.14 ± 1.6 and 33.5 ± 3.22 μm, on the particle size.…”
Section: Characterization Of the Microparticlesmentioning
confidence: 93%
See 3 more Smart Citations